Compensador série controlado a tiristores na distribuição: Compensação dinâmica - Almeida, Patrick Roberto de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
FACTS controllers (Flexible Alternating Current Transmission Systems) are capable of modifying the natural parameters of a transmission system to operate closed to the rated limits and delaying investments in the expansion these systems. In general, such devices can be series connected, shunt or a combination of both, allowing the correction of power system stability problems, voltage sags and swells, and others. In distribution systems, the reactive compensators, especially switched series capacitor banks and shunt capacitor banks as well as electronic controllers for many different purposes, has changed the classical topology, typically passive. For example, the thyristor controlled series compensators emerge as an alternative to fixed series compensation, allowing postpone of investments in distribution networks, substations, etc. This dissertation presents the D-TCSC (Distribution - Thyristor Controlled Series Compensator), a FACDS (Flexible Alternating Current Distribution Systems) controller which can be used as a solution to voltage control during connection of large loads, according the voltage levels established by PRODIST - Distribution Procedure

Controladores FACTS (Flexible Alternating Current Transmission Systems) são equipamentos capazes de modificar os parâmetros naturais de um sistema de transmissão, levando-os a operar próximo aos limites operacionais, de modo a postergar investimentos na ampliação destes sistemas. Em geral, tais equipamentos podem ser conectados em série, em derivação ou mesmo em uma combinação de ambos, permitindo a correção de possíveis problemas de estabilidade, de afundamento de tensão, entre outros. Nos sistemas de distribuição, a presença de compensadores de reativos, com destaque aos bancos de capacitores série e derivação chaveados, bem como de controladores eletrônicos para as mais diversas finalidades, tem alterado a topologia clássica, tipicamente passiva. Como exemplo, os compensadores série controlados a tiristor surgem como uma alternativa à compensação série fixa, possibilitando o adiamento de investimentos por parte das concessionárias de distribuição de energia em redes, subestações, etc. Esta dissertação apresenta o D-TCSC (Distribution - Thyristor Controlled Series Compensator) como dispositivo FACDS (Flexible Alternating Current Distribution Systems) em um sistema de distribuição como alternativa para controle de afundamentos de tensão durante a partida de grandes cargas, conforme os níveis de tensão de atendimento estabelecidos pelo PRODIST - Procedimento de Distribuição
Keywords: Energia elétrica - Distribuição; Sistemas de energia eletrica - Estabilidade; Controle por tiristores; Electric power distribution